Fake news - Mara, Wil (Global citizens: Modern media., 2019)
Examines incidents of fake news around the world both past and present, and discusses the effects of fake news on the world. Details ways to critically evaluate news and stop fake news from spreading. Includes a critical thinking question, color photographs, a glossary, and further resources.